Maternal Health, Children Education and Women Empowerment: Quasi-Experimental Evidence from India - Somdeep Chatterjee; Prashant Poddar (Global Labor Organization (GLO), 2019)
The empirical evidence on the inter-generational effects of maternal health interventions is inconclusive, particularly the impact on cognitive ability of children. In this paper, we study one such popular policy from India, viz, the Janani Suraksha Yojana (JSY) which is a agship health and safe motherhood program. We exploit plausible exogenous variation in exposure to the program generated by the institutional features of the implementation, in a cross-sectional difference-in-difference framework to find evidence of reduction in academic test scores of children whose parents remained unexposed to the policy intervention. We also find that such children spend less time on homework during the week, were less likely to attend and enjoy school. We also find negative effects on women empowerment measures for the unexposed women. The results suggest that the JSY led to increase in women empowerment and improved cognitive outcomes for children.
Keywords: D10; I18; I20; I38; 330; maternal health; women empowerment; children education